Milton's ontology, cosmogony and physics - Curry, Walter Clyde, 1887-1967 (University of Kentucky Press, 1957)
Walter Clyde Curry, a well-known student of Milton, analyzes the origins and unique construction of the grand stage upon which Milton presents the drama of human destiny in Paradise Lost. Through close examination of four entities -- Heaven of Heavens, Hell, chaos, and the World -- a greatly expanded view is provided of the poet's concept of space and God's relation to total creation. In facing structural and philosophical problems Milton is shown to be neither a materialist, nor an eclectic, nor a pantheist, as many scholars have insisted; he emerges rather as a master syncretist of widely divergent materials and as a devout theopantist. Curry has established a firm basis for a better understanding of the poet's methodology and for a clearer insight into his artistic accomplishments.